Discovering inspiring teaching: immersive models of staff development. Issue 3 (1st July 2014) - Hennessy, Claire; Adams, Gill; Mahon, Elizabeth; Nixon, Sarah; Pratt, Andrea; Williams, Louise
Abstract : Purpose: – The purpose of this paper is to outline an innovative method of delivering staff development in an higher education (HE) setting. The paper evaluates the processes behind the "Focus on Inspiring Teaching" week and outlines its initial impact on staff. Design/methodology/approach: – This is a descriptive case study which highlights how an immersive staff development event can be used to enable HE teaching practitioners to utilise more inspiring approaches to teaching and learning. The paper draws on questionnaire evaluations ( n = 43). Findings: – The paper highlights how staff development events can be used to foster communities of practice for teaching staff. For this to be successful, staff needs to be committed to reflecting on their own practice and be sufficiently engaged to partake actively of staff development events. By establishing these communities, inspiring practice in teaching can be developed with successful outcomes. The paper outlines a model for staff development which could be established in other HE settings. Practical implications: – Immersive staff development events are effective in achieving sustainable impact. To achieve success effective leadership and a team of committed teaching staff are needed. Success was also fostered by not making sessions compulsory whereby the staff could opt in for sessions to fit around teaching schedules. Originality/value: – This paper will be of interest to those working in staff development and training and academic managers. It indicates how immersive staff development can have a positive impact on staff practice to bring about improvements to the student experience.